Securitization in East Asia - Paul Lejot; Douglas Arner; Lotte Schou-Zibell (Asian Development Bank (ADB), 2008)
Securitization offers a range of benefits for Asia's financial systems and economies as a mechanism to assist funding and investment. As a form of structured finance, reliable and efficient securitization can assist development by enabling financial systems to deepen and strengthen - thus contributing to overall economic growth and stability. It must be recognized, however, that there are both overt and more subtle risks in certain uses of securitization. The credit and liquidity crisis that began in the United States and spread to other developed financial systems in mid-2007 exposed the danger associated with securitization: excessive risk-taking or regulatory capital arbitrage rather than a tool to assist more conventional or conservative approaches to funding, risk management, or investment. Securitization has also been criticized for rendering financial markets opaque, while contributing to a growing emphasis in the global economy of credit intermediation conducted in capital markets rather than through banks. This study examines the institutional basis of these concerns by investigating the use of securitization in East Asia, questioning both the growth in regional activity since the 1997/98 Asian financial crisis, and the reasons for it remaining constrained. The paper concludes with a discussion of proposals to support proper development of securitization in the region, including institutional mechanisms that could better allow securitization to enhance development and financial stability. If East Asia begins to make fuller use of securitization, its motive will be to meet funding or investment needs in the real economy rather than balance sheet arbitrage of the kind that peaked elsewhere in 2007.
hdl:11540/2360
Keywords: F30; G20; K20; 330; Securitization; East Asia; debt markets; risk transfer